THE CONCEPT AND APPLICATION OF COVENANT IN FINANCING GOLD PAWN BY SHARIA BANKS IN WEST JAVA - Neni Nuraeni; Dewi Sulastri; Z Zulbaidah (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: In Law Number 1 of 1974 Article 3 paragraphs 1 and 2, providing an explanation of the marriage principle is monogamous but is open, or in KHI using the term polygamy is limited to four wives, but with a record of the ability to provide and do justice towards his wives and children. Households that are built based on polygamy are part of a community that is a matter of controversy, but legal normativeity has been ratified and that a social reality occurs. The method is used in this study by collecting data in the form of literary literature (literature research), as for the steps in this study by reading literature in the form of books, articles, legislation and fatwas. The data is analyzed by qualitative descriptive method in order to obtain research results based on theories related to research The results showed that there were no women who were willing to be polygamous. In the case of polygamy, women are the object of violence wrapped neatly in household life. Abstrak: Salah satu bentuk inovasi yang dikeluarkan bank syariah untuk menunjang kebutuhan masyarakat adalah produk gadai emas syariah. Namun, kekhawatiran muncul terhadap produk rahn (gadai syariah) karena produk ini bukan merupakan aset produktif dalam menghasilkan keuntungan. Dengan adanya layanan ini, Bank Syariah hanya mendapatkan keuntungan dari jasa pemeliharaan barang yang dijanjikan sebagai jaminan. Permasalahan muncul ketika keuntungan diambil dari persentase besaran pinjaman yang diberikan oleh Bank Syariah kepada nasabah sebagaimana praktik di perbankan konvensional. Oleh karena itu, ini adalah topik yang menarik untuk dibahas di antara akademisi yang terkait dengan besaran dan perhitungan jasa pemeliharaan yang harus dibayar nasabah kepada Bank. Jika jasa pemeliharaan ditentukan berdasarkan persentase dari jumlah pembiayaan atau pinjaman, maka terdapat nilai bunga kredit atas pembiayaan yang harus dikembalikan oleh nasabah sebagai jasa pemeliharaan yang dihitung dari besaran pinjaman tersebut. Dengan demikian, penelitian ini dimaksudkan untuk menganalisa konsep akad dan penerapannya dalam pembiayaan gadai emas di bank syariah. Adapun obyek studi ini adalah mengenai bank komersial Islam, termasuk Bank Syariah Mandiri dan Bank Jabar Banten Syariah.